(untitled) (Malay Literature, 2012)
This article discusses aspects of identity building in the national literature of Sarawak. The author argues that the presence of a variety of authors in Sarawak is quite unique in expressing the ethnic diversity of Sarawak. This is because some of the ethnic writers include local colour in their writings. The situation is different in Peninsular Malaysia; although there are various ethnic groups such as Javanese, Banjar Bugis, Malaysian aborigines and Minang, there is little foregrounding of this in their writings, unlike what can be found in Sarawak. The ethnic diversity in Sarawak brings with it a number of ethnic issues, while at the same time representing problems that exist within these ethnic societies. The use of the national language in the works produced in Sarawak provides a national perspective without neglecting local issues that authors attempt to deal with. Authorship, theme and thinking, as well as the authors’ attitudes in the works are also discussed in order to look at the dimension of national authorship in the context of local knowledge. Keywords: national identity, ethnicity, authorship, national literature